An assessment of corporate social responsibility in South Africa's mining industry : a case study of Anglo American Platinum's corporate social investment programmes in the area of education - Siyobi, Busisipho Ayakha (Department of Political Studies, 2016)
The Corporate Social Responsibility (CSR) agenda and practice has been a part of the global, academic and corporate debate for many decades. Policymakers are increasingly viewing the private sector as an important role player in contributing towards meeting the socio-economic developmental challenges. The research study has assessed the role of CSR in South Africa's mining industry with a focus on the basic education system; by unpacking the objectives and the key challenges of the provincial department of basic education in the North West and Limpopo provinces. This research study has made use of Anglo American Platinum's Corporate Social Investment (CSI) education programmes as a case study to further gauge the impact of CSR engagement and key challenges that prevail in the execution of CSI education programmes. The challenges pertain to poor coordination and cooperation, poor consultation and strategic planning and lack of consistent review of monitoring and evaluation of all the stakeholders involved. Therefore, the paper argues that company's interests, incentives and motives to engage in CSI education programmes is twofold: one; CSI is used to project public relations and as a 'window-dressing' exercise and two; businesses are gradually viewing CSI as a long-term investment towards social and human capital that will benefit the corporations in the future.